2010
DOI: 10.1177/154193121005402104
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Compliance to In-Manual and On-Product Warnings

Abstract: Warnings have several purposes, including the communication of hazard information and promotion of safe behavior. The present study examined how compliance is affected by viewing duration of product manual warnings and the presence and content of on-product warnings for a computer memory installation task involving an electrostatic discharge hazard. Analyses showed that both the presence of an ANSI-style label and longer manual exposure increased behavioral compliance. The additive effect of exposure time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Warning features. Although prior research has described warning labels as being either consistent ("ANSI-style") or inconsistent with ANSI guidelines (Frantz et al, 2005;Shaver et al, 2006;Smith & Wogalter, 2010), the ANSI (2011) guidelines are composed of a collection of separable features. In order to analyze the relationships between these features and predicted noticing/compliance, we created binary variables for font size (0 = 17 point, 1 = 20 point), paragraph format (0 = continuous font, 1 = bulleted font), warning header (0 = orange header not present, 1 = orange header present), presence of a pictogram (0 = not present, 1 = present), and the presence of an alternative (modified image or ANSI-ISO blend) pictogram style (0 = not present, 1 = present).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Warning features. Although prior research has described warning labels as being either consistent ("ANSI-style") or inconsistent with ANSI guidelines (Frantz et al, 2005;Shaver et al, 2006;Smith & Wogalter, 2010), the ANSI (2011) guidelines are composed of a collection of separable features. In order to analyze the relationships between these features and predicted noticing/compliance, we created binary variables for font size (0 = 17 point, 1 = 20 point), paragraph format (0 = continuous font, 1 = bulleted font), warning header (0 = orange header not present, 1 = orange header present), presence of a pictogram (0 = not present, 1 = present), and the presence of an alternative (modified image or ANSI-ISO blend) pictogram style (0 = not present, 1 = present).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, research investigating the impact of safety labeling configuration on measures of warning effectiveness has produced somewhat conflicting findings. Some previous studies have reported that warning labels that are consistent with the ANSI Z535 guidelines are more effective than alternative warnings in terms of both predicted compliance (Laughery et al, 2002) and actual behavioral compliance (Smith & Wogalter, 2010). Other studies, however, have reported that the effectiveness of warning labels is contingent upon perceived risk (Heckman, Harley, Scher, & Young, 2010) and that ANSI-style warning labels can be less effective than both older OSHA-style warning labels (Kim & Wogalter, 2009) and more generic non-ANSI style warnings (Frantz, Young, Rhoades, & Wisniewski, 2005;Young, Frantz, Rhoades, & Darnell, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Laughery et al (2002) reported that warning labels that comply with ANSI Z535 guidelines are perceived as more likely to be noticed, read, understood and complied with as compared to non-compliant warnings. An experiment conducted by Smith and Wogalter (2010) provides support for the hypothesis that users are more likely to comply with on-product warning labels that are consistent with ANSI Z535 guidelines than generic warning labels. Conversely, other research suggests that both generic and ANSI-style warning labels are ineffective at inducing compliance in situations where perceived risk is low (Heckman, Harley, Scher, & Young, 2010), and that in some situations older OSHA-style warnings may be more effective than warnings that comport with more recent versions of the Z535 guidelines (Kim & Wogalter, 2009).…”
Section: Introductionmentioning
confidence: 87%